Threshold Relationship Between Geopolitical Risk And Islamic Financial Stability: Sbis-Fasbis Moderation - Sabaruddinsah Sabaruddinsah; Neng Asiah (Lentera Ilmu Nusantara, 2026)
This study examines the nonlinear associative relationship between geopolitical shocks and Islamic financial stability in Indonesia, incorporating the moderating roles of SBIS and FASBIS. Using monthly data from January 2015 to December 2024 and a threshold regression approach, the analysis reveals a state-dependent relationship between geopolitical risk and financial stability. A threshold effect is identified at a GPR value of 85.2 (95% confidence interval: 82.1–88.5). Below this level, the association is not statistically significant, whereas above it becomes significantly negative, indicating that the impact of geopolitical shocks materializes only beyond a critical intensity. SBIS exhibits conditional moderation, functioning as a stabilizing instrument at low GPR levels (threshold = 84.7) but becoming statistically insignificant under high geopolitical pressure. FASBIS shows a similar conditional pattern with a higher threshold (89.3), acting as a stabilizer at low GPR while losing effectiveness at higher levels without becoming counterproductive. The higher threshold associated with FASBIS provides descriptive evidence of greater resilience under elevated risk, although this comparison is not inferential. These findings provide robust evidence that the effectiveness of Islamic monetary instruments is inherently state-dependent, implying that linear models may obscure regime-specific dynamics. Policy implications include integrating geopolitical risk into early warning systems and strengthening liquidity facilities during periods of heightened uncertainty.